Toxicological evaluation of volatile organic compounds emitted from scented candles: in silico ADMET profiling, oxidative stress, inflammation, and lung injury in rats - Mohamed, Mervat S.; Omran, Awatif M. E.; Obidan, Amnah; Alsulami, Seham O.; Aljohani, Nuha B.; Alshehri, Eman H.; Alfarteesh, Hajer; Aljohani, Norah Bakheet; Ali, Ayat G. (Frontiers in Public Health, 2025)
Scented candles are widely used in the Middle East, particularly in the Arab Gulf region, to enhance indoor environments. However, limited ventilation in enclosed air-conditioned spaces can cause emissions to accumulate, posing health risks. Although the chemical composition of candle emissions has been examined, their in vivo toxicological effects under realistic exposure conditions remain unclear. This study evaluated the toxicity of scented candle emissions in male Wistar rats. Fifty-four rats were divided into nine groups (n = 6/group): controls exposed to fresh air, unscented candle emissions, or scented candle emissions for 1, 3, or 6 h daily, 5 days per week for 8 weeks under indoor-like conditions. GC–MS analysis identified 20 volatile organic compounds (VOCs) in unscented and 60 in scented candles. In silico ADMET profiling predicted toxicity for several compounds. Biochemical assays showed elevated serum TNF-α and IL-6, increased MDA, and reduced CAT and T-SOD activities in lung tissue, indicating systemic inflammation and oxidative stress. qRT-PCR and immunohistochemistry confirmed upregulation of inflammatory markers (TNF-α, COX-2). Histopathology revealed inflammatory infiltration, fibrosis, and necrobiotic changes, particularly in scented candle-exposed groups. Chronic scented candle exposure in poorly ventilated spaces causes inflammation, oxidative stress, and lung injury.